Influence of plant growth regulators on fruit drop, fruit retention and fruit yield of mango (Mangifera indica l.) cv. Amrapali under west central table land zone of Odisha - Kundu, Amit Kumar; Tarai, Ranjan Kumar; Nayak, Amrutanshu; Senapati, Bhadratanu (Plant Science Today, 2024)
Farmers in the western region of Odisha are grappling with issues related to low fruit set, fruit drop, and erratic yield in mango cultivation. Plant growth regulators (PGRs) play a pivotal role in addressing fruit drop at different developmental stages by modulating the nutritional and hormonal status of the plant. This study aims to investigate the impact of specific PGRs on fruit drop, fruit retention, and overall yield of Mango (Mangifera indica L.) cv. Amrapali in the West Central Table Land zone of Odisha. The experimental setup was implemented at the research plot of the College of Horticulture, Chiplima, Sambalpur, following a randomized block design with ten treatments, each replicated three times. The treatments involved various concentrations of three PGRs: NAA, GA3, and 2,4-D, applied during the pea and marble stages of fruit growth. The outcomes indicated that the application of 30 ppm GA3 significantly mitigated fruit drop, with comparable efficacy observed for 30 ppm 2,4-D. GA3 positively influenced fruit retention, particularly Treatment T7 (30 ppm GA3), exhibiting the highest retention percentages at 30, 60, and 90 days post-spraying. Furthermore, GA3 at 30 ppm resulted in the maximum average fruit weight and volume. The highest number of harvested fruits per plant and maximum yield per plant were recorded in Treatment T7. These findings underscore the potential of GA3 in alleviating fruit drop, enhancing fruit retention, and improving overall yield in mango cultivation, specifically for the Amrapali variety in the West Central Table Land Zone of Odisha.